2009
DOI: 10.1016/j.ijgo.2009.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Use of prenatal corticosteroids for preterm birth in three Latin American countries

Abstract: Objective To determine the prevalence of the use of prenatal corticosteroids in women who delivered prematurely in 3 Latin American counties and to evaluate the maternal characteristics associated with use. Methods A multicenter, prospective, descriptive study was conducted in 4 hospitals in Ecuador, 5 in Uruguay, and 3 in El Salvador between 2004 and 2008. Women who had delivered between 24 and 34 weeks of pregnancy responded to a questionnaire assessing sociodemographic characteristics, obstetric history, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
(5 reference statements)
2
5
0
Order By: Relevance
“…In the present study of women who delivered between 24-and 34-weeks' gestation, only 35.3% were administered ACS. This is consistent with a study conducted in Ecuador [26]. In contrast, some studies conducted in low-and middle-income countries have also reported low rates of ACS use, e.g in Malawi (10%), Democratic Republican of Congo (16%), Nepal (20%), Uganda (27%), Nigeria (30%) and Kenya (32%) [27,28], while others conducted in South East Asia have reported a higher use of ACS (40%) [29].…”
Section: Plos Onesupporting
confidence: 93%
“…In the present study of women who delivered between 24-and 34-weeks' gestation, only 35.3% were administered ACS. This is consistent with a study conducted in Ecuador [26]. In contrast, some studies conducted in low-and middle-income countries have also reported low rates of ACS use, e.g in Malawi (10%), Democratic Republican of Congo (16%), Nepal (20%), Uganda (27%), Nigeria (30%) and Kenya (32%) [27,28], while others conducted in South East Asia have reported a higher use of ACS (40%) [29].…”
Section: Plos Onesupporting
confidence: 93%
“…Regardless of around 90% of providers reporting that they use ACT in TPL, information obtained from women having preterm births in the same hospitals showed figures of 34.8%, 54.6%, and 71% in Ecuador, El Salvador and Uruguay, respectively of ACT use [9]. Reasons explaining such discrepancy needs to be subject of analysis and actions to improve the reception of ACT on pregnancies that finally end in preterm birth.…”
Section: Resultsmentioning
confidence: 99%
“…Ecuador had the lowest use (34.8%), followed by El Salvador (54.6%), and Uruguay (71%) and the maternal characteristics associated with their use [9]. …”
Section: Introductionmentioning
confidence: 99%
“…In this study, all moms at risk of preterm delivery received betamethasone, the sole prenatal corticosteroid administered. In contrast to studies conducted around the world, where prenatal corticosteroids use ranged between 40% and 70% [7][8][9] in impoverished countries and 70-80% [10,11] in wealthy countries, the prevalence of use of antenatal corticosteroids was 70% in the Prathima labor ward. Just 10% of pre-term infants in low-and middle-income countries presently get prenatal corticosteroids.…”
Section: Discussionmentioning
confidence: 60%